ISU KONTEMPORER: GEREJA DAN PEKERJAAN BAIK - Noh Ruku (Departemen Literatur dan Media, Sekolah Tinggi Teologi Arrabona Bogor, 2019)
The church as a fellowship of people who believe in Jesus Christ as Lord and Savior in the midst of this world, can be an example of good deeds so that they can have a positive impact in accordance with God's Word.